DETERMINAN PENYERAPAN TENAGA KERJA - Lestari, Putu Ayu; Dewi, Made Heny Urmila (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023DO - 10.24843/BSE.2025.v30.i01.p09, 2025)
Judging from the TPAK data in Indonesia, especially the Province of Bali, it continues to experience a drastic increase, namely the highest in 2021 of 2,580,523 people. This drastic increase is not matched by the absorption of labor which will cause unemployment. Absorption of labor in an area is influenced by several factors, namely gross regional domestic product, education, and minimum wages. The purpose of this study is to analyze the effect of regional gross domestic product, education, and minimum wages on employment in the districts/cities of Bali Province. The data collection method uses non-participatory observation methods and the analysis technique used is panel data regression. The results of this study found that regional gross domestic product, education, and minimum wages simultaneously affect employment. Partially gross regional domestic product has a positive and significant effect on employment absorption, the minimum wage partially has a negative and insignificant effect on employment absorption. Meanwhile, education has a positive and insignificant effect on employment. Suggestions from this study from the workforce aspect, it is hoped that the government will give more focus to improving the quality of society, especially the working age population by providing educational services and education improvement programs.